The Demographic Transformation in Maine (and Beyond) Is in Full Swing - Kaye, Lenard (Maine Policy Review, 2015)
The article discusses the demographics of longevity and what it means for Maine. Lenard Kaye, guest editor, introduces the topic and describes the reasons for this special aging-focused issue of the Maine Policy Review.
Keywords: aging; Maine; demographics